2010
DOI: 10.1111/j.1540-5885.2010.00723.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Information Technologies in Enhancing R&D-Marketing Integration: An Empirical Investigation

Abstract: The effective integration of research and development (R&D) and marketing contributes to the development of successful new products. Barriers such as physical separation of R&D and marketing, goal incongruity, and cultural differences hamper the cross-functional cooperation. However, it may not be either possible or desirable to eliminate the cross-functional integration barriers in practice. Previous research findings suggest that information technology (IT) can be used to reduce the negative impact of the ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0
14

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(81 citation statements)
references
References 78 publications
(165 reference statements)
1
66
0
14
Order By: Relevance
“…Establishing such a communication climate helped to mitigate any in-group/out-group distinctions and faultlines that had formed in the design teams along national or other subgroup boundaries. Song & Song (2010) found not only that CMC tools can be used to reduce the negative impact of barriers, such as physical separation and cultural differences, in virtual teams, but also that it is important to look at the different types of IT systems being used. Rather than grouping all CMC tools together and examining the effects of electronic dependence, different categories of electronic tools may work differently to reduce the negative impact of physical separation and cultural differences on team outcomes (cf.…”
Section: Global Virtual Teamsmentioning
confidence: 99%
See 1 more Smart Citation
“…Establishing such a communication climate helped to mitigate any in-group/out-group distinctions and faultlines that had formed in the design teams along national or other subgroup boundaries. Song & Song (2010) found not only that CMC tools can be used to reduce the negative impact of barriers, such as physical separation and cultural differences, in virtual teams, but also that it is important to look at the different types of IT systems being used. Rather than grouping all CMC tools together and examining the effects of electronic dependence, different categories of electronic tools may work differently to reduce the negative impact of physical separation and cultural differences on team outcomes (cf.…”
Section: Global Virtual Teamsmentioning
confidence: 99%
“…Moreover, of the 392 papers on virtual teams, only 18 (4.6%) assessed nation or culture and included it in empirical analyses (i.e., Edwards & Sridhar 2005;Gibson & Gibbs 2006;Glikson & Erez 2013;Graf et al 2010;Hinds & Mortensen 2005;Jarvenpaa & Keating 2011;Krumm et al 2013;Martins & Shalley 2011;Mortensen & Hinds 2001;Muethel et al 2012a,b;Polzer et al 2006;Sarker 2005;Shachaf 2005;Song & Song 2010;Staples & Zhao 2006;Swigger et al 2004;Vignovic & Thompson 2010) (see Table 1). Of these, only 8 papers (2.0% of the total) measured both national culture and either electronic dependence or computer-mediated communication (CMC) tools (i.e., Edwards & Sridhar 2005, Gibson & Gibbs 2006, Glikson & Erez 2013, Martins & Shalley 2011, Muethel et al 2012b, Song & Song 2010, Staples & Zhao 2006, Swigger et al 2004). The other 10 included a simple comparison between teams who have no FTF interaction and teams who are completely FTF (for meta-analytic reviews, see Fjermestad 2004 andRains 2005).…”
Section: Introductionmentioning
confidence: 99%
“…It can focus attention to the tasks at hand rather than dealing with potential conflict and divergent perspectives which may come to the surface when interpersonal communication is predominant. This builds upon the work of Song and Song (2010) who found that more asynchronous communication can help reduce the negative effects of disagreements during development. (Thatcher and Brown, 2010).…”
Section: Interaction Effectsmentioning
confidence: 79%
“…Cross-functional coordination has been frequently recognized as a critical factor for successful technological innovation or new product development (Ayers, Dahlstrom, & Skinner, 1997;De Clercq et al, 2011;Song & Montoya-Weiss, 2001;Song & Parry, 1997;Song & Song, 2010;Stock et al, 2013;Suder, Sherman, & Davis-Cooper, 1998;Troy et al, 2008;Xie et al, 2003). Cross-functional coordination refers to the extent of interaction, communication, information sharing, and joint involvement across diverse organizational functions such as R&D, production, and marketing (Song & Montoya-Weiss, 2001;Troy et al, 2008).…”
Section: B Cross-functional Coordination and Technological Innovatiomentioning
confidence: 99%